Relationship Between Service Performance And Financial Performanceon The Level Of Financial Independence At The Central General Hospital H. Adam Malik Medan - Arthur Simanjuntak; Duma Megaria Elisabeth; Dimita HP Purba; Rike Yolanda Panjaitan; Putri Sopianna Sianturi (Jurnal Ilmiah Accusi, 2024)
The intention of these researchers is to study the relationship between economic performance and service performance at the level of independence at H. Adam Malik Central General Hospital. Secondary data is used in this research, which is a quantitative approach. Order of population members based. The sample for study is financial reporting data and services at RSUP H. Adam Malik Medan for the years 2018 - 2022. From the results of this study, it appears that there is a link between economic performance, measured by the correlation of Fixed Asset Turnover (PAT) and service performance, measured by mean length of stay (AVLOS), and the degree of autonomy of the public There are hospitals. 2018 - 2022 Center H. Adam Malik